2018
DOI: 10.1017/s0007114518000430
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C intake in relation to bone mineral density and risk of hip fracture and osteoporosis: a systematic review and meta-analysis of observational studies

Abstract: We aimed to systematically review available data on the association between vitamin C intake and bone mineral density (BMD), as well as risk of fractures and osteoporosis, and to summarise this information through a meta-analysis. Previous studies on vitamin C intake in relation to BMD and risk of fracture and osteoporosis were selected through searching PubMed, Scopus, ISI Web of Science and Google Scholar databases before February 2017, using MeSH and text words. To pool data, either a fixed-effects model or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 68 publications
2
56
1
2
Order By: Relevance
“…Finally, our pooled-effects analysis revealed a negative correlation between DIVCF and risk of hip fracture (RR, 0.66; 95% CI, 0.47-0.94); i.e., subjects with a higher intake of Vitamin Coriented foods had a 34% (95% CI, 6%−53%) lower risk of hip fracture (Figure 2). Our results differ from those of Dr. Malmir, published in April 2018 (27). Due to the major heterogeneity among the studies, we performed subgroup analyses based on study type (i.e., cohort and case-control studies), gender, and age (middle-aged subjects, older subjects).…”
Section: Comparison Of the Findings With Other Results In The Literaturecontrasting
confidence: 85%
See 1 more Smart Citation
“…Finally, our pooled-effects analysis revealed a negative correlation between DIVCF and risk of hip fracture (RR, 0.66; 95% CI, 0.47-0.94); i.e., subjects with a higher intake of Vitamin Coriented foods had a 34% (95% CI, 6%−53%) lower risk of hip fracture (Figure 2). Our results differ from those of Dr. Malmir, published in April 2018 (27). Due to the major heterogeneity among the studies, we performed subgroup analyses based on study type (i.e., cohort and case-control studies), gender, and age (middle-aged subjects, older subjects).…”
Section: Comparison Of the Findings With Other Results In The Literaturecontrasting
confidence: 85%
“…In this paper, we carried out a meta-analysis of the possible protective effect of DIVCF against osteoporosis, fracture, and BMD loss. A similar article (27) was published in April 2018. The authors found no significant association between Vitamin C intake and the risk of hip fracture (RR, 0.74; 95% CI, 0.51-1.08).…”
Section: Comparison Of the Findings With Other Results In The Literaturementioning
confidence: 80%
“…Ascorbic acid is known to stimulate collagen synthesis and secretion (16,27), enhance healing of fractured bones in preclinical studies (30), and significantly decrease the risk of osteoporosis and hip fracture in adults (31,32). Because mice differ from humans and fish by being able to synthesize de novo vitamin C, supplementation did increase bone mass but not in a statistically significant fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C plays a critical role in the development and maintenance of bone where it increases the rates of both procollagen hydroxylation and secretion. Prior work has confirmed the importance of vitamin C in maintaining bone health by demonstrating a positive association with vitamin C intake and BMD at the femoral neck and lumbar spine along with a 33% lower risk of osteoporosis [ 24 ]. These effects may stem from the suppression of osteoclast activity and the differentiation of osteoblasts by vitamin C [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%